2009
DOI: 10.1073/pnas.0902919106
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of triadin causes loss of cardiac Ca 2+ release units, impaired excitation–contraction coupling, and cardiac arrhythmias

Abstract: Heart muscle excitation-contraction (E-C) coupling is governed by Ca 2؉ release units (CRUs) whereby Ca 2؉ influx via L-type Ca 2؉ channels (Cav1.2) triggers Ca 2؉ release from juxtaposed Ca 2؉ release channels (RyR2) located in junctional sarcoplasmic reticulum (jSR). Although studies suggest that the jSR protein triadin anchors cardiac calsequestrin (Casq2) to RyR2, its contribution to E-C coupling remains unclear. Here, we identify the role of triadin using mice with ablation of the Trdn gene (Trdn ؊/؊ ). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
174
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 34 publications
13
174
0
Order By: Relevance
“…Comparison of the results reported in Figures 2A and 2B suggested that TD32 levels decreased due to the lack of functional CSQ2 from birth in the CSQ2-R33Q/R33Q mice. Results from a previous study (19) also showed that CSQ2 protein levels were significantly reduced in adult Trdn -/-mice. The mechanism of the post-transcriptional control of unfolded proteins can explain the reduction of CSQ2-R33Q protein levels without any effect on mRNA content.…”
Section: Discussionsupporting
confidence: 49%
“…Comparison of the results reported in Figures 2A and 2B suggested that TD32 levels decreased due to the lack of functional CSQ2 from birth in the CSQ2-R33Q/R33Q mice. Results from a previous study (19) also showed that CSQ2 protein levels were significantly reduced in adult Trdn -/-mice. The mechanism of the post-transcriptional control of unfolded proteins can explain the reduction of CSQ2-R33Q protein levels without any effect on mRNA content.…”
Section: Discussionsupporting
confidence: 49%
“…In myocytes lacking triadin, junctional SR proteins (RyR2, Casq2, junctin and junctophilin) were decreased and Casq2 occurred outside of the junctional SR. [5] Additionally, electron micrographs showed reduced frequency of junctional SR cisternae and shorter RyR2 containing contacts, with a~50% reduction in contacts between the junctional SR and the t tubules [5]. Levels [5]. Further experiments in which SR Ca 2+ release was disabled (using the SR inhibitors ryanodine or thapsigargin) abolished differences in I CaL inactivation between wildtype and TRDN −/− myocytes, supporting this explanation [5].…”
Section: The Role Of Triadin-1 In Ventricular Myocytessupporting
confidence: 58%
“…In cardiac muscle, TRDN deletion has been reported to alter the structure of the CRU [5]. In myocytes lacking triadin, junctional SR proteins (RyR2, Casq2, junctin and junctophilin) were decreased and Casq2 occurred outside of the junctional SR. [5] Additionally, electron micrographs showed reduced frequency of junctional SR cisternae and shorter RyR2 containing contacts, with a~50% reduction in contacts between the junctional SR and the t tubules [5]. Levels [5].…”
Section: The Role Of Triadin-1 In Ventricular Myocytesmentioning
confidence: 99%
See 2 more Smart Citations